Takayasu arteritis: an update - DİRESKENELİ, RAFİ HANER (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2022)
Takayasu arteritis (TAK) is a challenging chronic, granulomatous, large-vessel systemic vasculitis, mostly due to difficulties in early diagnosis and assessing actual disease activity. Since there are no specific diagnostic laboratory tests, biomarkers, or autoantibodies, many patients experience considerable delay in diagnosis. Remembering the possibility of TAK together with the use of acute phase responses and appropriate imaging studies may be helpful for early diagnosis. Since there may be discrepancies between systemic and vascular wall inflammation, using only acute phase responses is not reliable in assessing current disease activity. Therefore, physical examination and new imaging findings should also be used to assess current disease activity. Despite its limitations, the Indian Takayasu Clinical Activity Score (ITAS2010) may also be helpful for this purpose. The rationale of medical treatment is to suppress both vascular and systemic inflammation with appropriate systemic immunosuppression, including corticosteroids and conventional immunosuppressive agents. In cases of refractory disease activity, leflunomide and biologic agents such as TNF inhibitors and tocilizumab may be tried. In selected cases with persistent lesions that cannot be reversed with medical treatment, endovascular interventions including balloon angioplasty, stent and stent graft replacement, or surgery may be tried. However, such procedures should be performed after suppression of inflammation, i.e. during inactive disease. Prognosis of TAK is probably getting better with lower mortality rates reported in recent years, probably due to the use of more effective medical treatments as well as the use of endovascular interventions when necessary and available.
Keywords: Takayasu arteritis; large vessel vasculitis; management; diagnosis; disease activity; GIANT-CELL ARTERITIS; LARGE-VESSEL VASCULITIS; TERM-FOLLOW-UP; CLINICAL ACTIVITY SCORE; NECROSIS FACTOR THERAPY; OF-THE-ART; DISEASE-ACTIVITY; PYODERMA-GANGRENOSUM; AORTIC-WALL; IMMUNOSUPPRESSIVE THERAPY